The Use of Camtasia Video, Youtube, and WhatsApp in Online Teaching During Pandemic Situation - Tri Wahyuni Chasanatun; Sri Lestari (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
The aims of this article is to discuss about the implementation of Camtasia and YouTube in Teaching Writing for English Department Students. The problem of the writer in teaching writing for first semester of English Department students in this pandemic situation is online learning media. Not only learning media, but also for the students who lives in rural area are faced the difficulties to get the internet connection easily if the online learning done through Google meet or Zoom. In order to solve that problem, the writer proposes Camtasia, YouTube, and also WhatsApp to deliver the learning material.  Camtasia, YouTube, and WhatsApp is an application that can be used as a learning media. Camtasia itself is used to record the material in the form of video or PPT presentation. After finish recording the material, the Camtasia Video can be shared to the students through YouTube Channel. Then the last step is shared the link through WhatsApp group and continued with discussion session. The Subject of this research is first semester students of English Department Program. The research is done start from August to December 2020. This research is qualitative research. The data for this research are taken form the observation and also interview. The results of this research are: After the implementation of Camtasia, you tube link, and also create the discussion on WA group, more than 95% students are able to write with correct punctuation and use capital letter in their sentences, especially in the beginning of their sentence. Moreover, the students are also able to make a sentences with good arrangement by choosing effective words and appropriate order. Only 3 students who still difficult to develop their idea on writing in a good organization, grammatical order, and content.